2017
DOI: 10.1371/journal.pone.0185876
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center study on patient selection for and the oncologic safety of intraoperative radiotherapy (IORT) with the Xoft Axxent® eBx® System for the management of early stage breast cancer in Taiwan

Abstract: BackgroundIn this multi-center study, we report the patient selection criteria for and preliminary oncologic outcomes associated with intraoperative radiotherapy (IORT) delivered by the Xoft Axxent® eBx® system for early-stage breast cancer in Taiwan.MethodsPatients with early breast cancer in Taiwan received breast conserving surgery and received IORT with Xoft Axxent® eBx® System during 2013–2015 was search from database of Taiwan IORT study cooperative group (T-IORTSCG). Patients’ clinicopathologic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
2
12
0
1
Order By: Relevance
“…However, our results show that the prescription dose underestimates the physical absorbed dose to water, which has profound implications for studies investigating the relationships between dose and therapeutic effect from INTRABEAM, or comparing INTRABEAM treatments with other radiation delivery methods. Relevant examples of comparing outcomes with other radiation treatment types include breast IORT treatments performed with the Xoft Axxent source (ClinicalTrials.gov Identifier: NCT01644669), or treatments combining INTRABEAM IORT with external beam radiotherapy (TARGIT‐B trial, ClinicalTrials.gov Identifier: NCT01792726).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results show that the prescription dose underestimates the physical absorbed dose to water, which has profound implications for studies investigating the relationships between dose and therapeutic effect from INTRABEAM, or comparing INTRABEAM treatments with other radiation delivery methods. Relevant examples of comparing outcomes with other radiation treatment types include breast IORT treatments performed with the Xoft Axxent source (ClinicalTrials.gov Identifier: NCT01644669), or treatments combining INTRABEAM IORT with external beam radiotherapy (TARGIT‐B trial, ClinicalTrials.gov Identifier: NCT01792726).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Takanen et al reported that the 5‐year post‐IORT local recurrence rate in patients older than 50 years was lower than 2%. The results were good even in centers with more liberal selection criteria that included younger patients with larger tumors . We found that after a mean of 30 months, there were no cases of local recurrence among the patients who met the hospital's eligibility criteria for IORT.…”
Section: Discussionmentioning
confidence: 75%
“…Lastly, researchers who conducted a multi-institutional study including 41 patients with DCIS among a cohort of more than 250 patients with breast cancer treated with the Xoft eBx ® system reported 2 recurrences among their patients with DCIS (4.9%) at a short follow-up of 16 months. 13 Interestingly, the patients in this study were significantly younger compared with TARGIT-A and ELIOT patients, with 16.5% of the patient cohort <45 years old. It is unclear what percentage of patients in these studies would be deemed suitable for APBI according to American Society for Radiation Oncology (ASTRO) guidelines.…”
Section: Introductionmentioning
confidence: 64%
“…This is comparable to other reports of DCIS managed with intraoperative therapy. 11 , 13 The majority of our patients were considered cautionary for APBI according to ASTRO guidelines because of the presence of high-grade DCIS. Deconstructing the proposed guidelines into preoperative and postoperative criteria specifically for application to patient selection for IORT, we found a shift in approximately 15% of our patients to a less suitable CG group based on final lumpectomy pathologic examination (9.5% among suitable patients, 22% among cautionary patients).…”
Section: Discussionmentioning
confidence: 99%